The moment of clarity : - Madsbjerg, Christian (Harvard Business Review Press, 2014)
Christian Madjsberg and Mikkel Rasmussen, principals at ReD Associates, argue for the role of a new set of tools to understand the "soft" factors that influence how people buy and consume ideas and products. Drawn from the authors' work with companies like Lego, Samsung, Adidas, Intel, IBM, and Coke, the book will teach you how to understand people holistically in their environments-how they live, what they think and do all day, what their habits are, and how they understand the world. For brand fanatics and business leaders alike.